2016
DOI: 10.5430/ijfr.v8n1p112
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Geography of Human Capital in Twentieth-Century Latin America

Abstract: In this paper we present results for educational achievement in the different economic regions of Latin America (Big countries: Mexico and Brazil; Southern Cone; Andean countries; Central America; and others) during the twentieth century. The variables we use to measure education are average years of education, literacy, average years in primary school, average years in secondary school, and average years in university. To attain a broader perspective on the relationship of education with human capital and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…With panel data, several studies have confirmed the positive relationship between education capital and economic growth, including Barro ( 1996 , 1996 , 2001 ), Agiomirgianakis et al ( 2002 ), Jamison, et al ( 2007 ), Li and Huang ( 2009 ), Hanushek and Woessmann ( 2011 ), Zhang and Zhuang ( 2011 ), Hanushek ( 2013 ), Siddiqui and Rehman ( 2016 ), and Zhang and Wang ( 2021 ). With time-series data, we can observe also that education stock was more prominent in explaining the fluctuations of economic growth (Musila & Belassi, 2004 ; Dauda, 2010 ; Jalil & Idrees, 2013 ; Qadri & Waheed, 2014 ; Breton, 2015 ; Camps & Engerman, 2017 ; Dhrifi et al, 2021 ; Awad, 2021 ).…”
Section: Related Literaturementioning
confidence: 98%
“…With panel data, several studies have confirmed the positive relationship between education capital and economic growth, including Barro ( 1996 , 1996 , 2001 ), Agiomirgianakis et al ( 2002 ), Jamison, et al ( 2007 ), Li and Huang ( 2009 ), Hanushek and Woessmann ( 2011 ), Zhang and Zhuang ( 2011 ), Hanushek ( 2013 ), Siddiqui and Rehman ( 2016 ), and Zhang and Wang ( 2021 ). With time-series data, we can observe also that education stock was more prominent in explaining the fluctuations of economic growth (Musila & Belassi, 2004 ; Dauda, 2010 ; Jalil & Idrees, 2013 ; Qadri & Waheed, 2014 ; Breton, 2015 ; Camps & Engerman, 2017 ; Dhrifi et al, 2021 ; Awad, 2021 ).…”
Section: Related Literaturementioning
confidence: 98%